(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2021)
This autoethnographic essay discusses the author’s experiences and reflections on teaching and learning in a college town in the southern US in Spring 2020. What happens to faculty and students and the work of teaching and learning during an unprecedented event such as a pandemic? How do we work alongside the disruptions of everyday routines and suddenly navigate massive social change? The author describes some of the issues that a teacher and her students navigated personally and professionally during a semester of crisis precipitated by a global pandemic.